Sustainability of affordable housing programs in Kenya: A case of Meru and Embu Counties - Karambu Kiende Gatimbu; Paul Njiru Nthakanio (PLoS ONE, 2026)
Amid rising urbanization and population growth, Kenya faces a critical housing shortage that disproportionately affects low- and middle-income populations. In response, the government launched the Affordable Housing Program (AHP) under the Big Four Agenda to address this housing gap. This study evaluates the sustainability of AHP projects in Meru and Embu counties, focusing on economic, social, and environmental dimensions. Using a descriptive research design, data were collected from 215 purposively selected participants comprising members of the public, academics, and contractors. Quantitative data were analyzed using Stata 18, including descriptive statistics, factor analysis, and Generalised Linear Models (GLMs). The results indicate that while the AHP has made significant progress in improving housing affordability and social safety, challenges remain, particularly in environmental sustainability, stakeholder engagement, and the use of local materials. Safety, security, and affordability ranked highest across respondents, whereas features such as lift access and energy-efficient systems were ranked lower. The findings also highlight demographic differences in sustainability preferences: older respondents emphasized safety and infrastructure reliability, whereas postgraduate respondents prioritized environmental sustainability. The study recommends stronger stakeholder involvement, localization of policy frameworks, and integration of green building standards. These insights provide valuable guidance for policymakers and practitioners seeking to scale sustainable housing solutions in Kenya and similar developing contexts.